Legal Certainty of the Transfer of Collection Rights (Cessie) in the Process of Postponement of Debt Payment Obligations (PKPU) and Bankruptcy Without Notification to the Debtor - Moh Yusuf Pradhana; Dewi Iryani; Puguh Aji Hari Setiawan (Green Publisher Indonesia, 2026)
The transfer of collection rights through the cessie mechanism is a common legal practice used in receivables transactions. However, in the context of the Suspension of Debt Payment Obligations (PKPU) and bankruptcy, the practice of cessie carried out without notice to the debtor still causes legal uncertainty, especially related to the protection of the rights of the parties. This study aims to analyze the legal arrangement of cessie without notification to the debtor based on applicable regulations and examine the form of legal protection for creditors in the PKPU and bankruptcy process. The research method used was normative juridical with a legislative approach and a conceptual approach. Research data was obtained through a literature study of relevant laws and regulations, legal doctrines, and court decisions. The results of the study show that the provisions of Article 613 of the Civil Code recognize the validity of cessie even without notification to the debtor, but sectoral regulations, especially Financial Services Authority Regulation Number 22 of 2023, require the debtor's notification or consent as a form of consumer protection. These differences in regulation give rise to legal dualism that has the potential to reduce legal certainty in PKPU and bankruptcy practices. This study concludes that regulatory harmonization is needed to ensure legal certainty and justice for creditors and debtors in the transfer of billing rights through cessie.